2021
DOI: 10.3389/fonc.2021.778637
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Model Using Alternative Splicing Events and the Immune Microenvironment Signature in Lung Adenocarcinoma

Abstract: BackgroundAlternative splicing (AS) is a gene regulatory mechanism that drives protein diversity. Dysregulation of AS is thought to play an essential role in cancer initiation and development. This study aimed to construct a prognostic signature based on AS and explore the role in the tumor immune microenvironment (TIME) in lung adenocarcinoma.MethodsWe analyzed transcriptome profiling and clinical lung adenocarcinoma data from The Cancer Genome Atlas (TCGA) database and lists of AS-related and immune-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Many prognostic models for LUAD based on gene features have been developed, such as a tumor microenvironment-associated prognostic signature introduced by Zhao et al (47), a sevenimmune-related-gene signature constructed by Zhan et al (59), and an alternative splicing-related prognostic model proposed by Zhu et al (60). Compared with these models, our study reported a prognostic model based on IARGI, which showed good prognostic accuracy for LUAD.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Many prognostic models for LUAD based on gene features have been developed, such as a tumor microenvironment-associated prognostic signature introduced by Zhao et al (47), a sevenimmune-related-gene signature constructed by Zhan et al (59), and an alternative splicing-related prognostic model proposed by Zhu et al (60). Compared with these models, our study reported a prognostic model based on IARGI, which showed good prognostic accuracy for LUAD.…”
Section: Discussionmentioning
confidence: 81%
“…( 47 ), a seven-immune-related-gene signature constructed by Zhan et al ( 59 ), and an alternative splicing-related prognostic model proposed by Zhu et al. ( 60 ). Compared with these models, our study reported a prognostic model based on IARGI, which showed good prognostic accuracy for LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…RAS signalling is an important mechanism for regulating the diversities of gene expression and the proteome amongst eukaryotes [39]. However, abnormal expression of RAS in cells may lead to the development of various diseases, such as atherosclerosis as well as lung and pancreatic adenocarcinoma [40,41]. Research has also shown that aberrant RAS is one of the leading factors involved in the regulation of AML drug resistance, and it is usually closely associated with poor prognosis and drug resistance in AML [42].…”
Section: Discussionmentioning
confidence: 99%